1996
DOI: 10.1002/(sici)1096-8628(19960216)67:1<63::aid-ajmg11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor gene: Organization, transcript variants, and polymorphism associated with schizophrenia

Abstract: DNA fragments from a genomic library were used to establish the partial structure of the human dopamine D3 receptor gene (DRD3). Its coding sequence contains 6 exons and stretches over 40,000 base pairs. The complete DRD3 transcript and three shorter variants, in which the second and/or third exon are deleted, were detected in similar proportions in brains from four controls and three psychiatric patients. The Msp I polymorphism was localized in the fifth intron of the gene, 40,000 base pairs downstream the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 30 publications
1
31
2
1
Order By: Relevance
“…In addition, the sample used in the present (ISHDSF) study is strongly familial and therefore should have easily detected the effect. As with the Welsh sample, the French sample was also subsequently enlarged, 9 but the strength of the original association reported in Crocq et al 10 (Chi-square = 6.96, d.f. = 1, P = 0.008) was weakened (Chi-square = 5.3, d.f.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the sample used in the present (ISHDSF) study is strongly familial and therefore should have easily detected the effect. As with the Welsh sample, the French sample was also subsequently enlarged, 9 but the strength of the original association reported in Crocq et al 10 (Chi-square = 6.96, d.f. = 1, P = 0.008) was weakened (Chi-square = 5.3, d.f.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is mapped to chromosome 3q13.3; the coding sequence is 661 bp in length and contains six exons. 9 Association studies of DRD3/MscI polymorphism (Serine-9-Glycine substitution) and schizophrenia have produced interesting but conflicting findings. In a study of Welsh and French schizophrenic patients, significant association was observed between the disease and homozygosity for DRD3 variants 1-1 and 2-2.…”
Section: Introductionmentioning
confidence: 99%
“…The single gene coding for the D3 receptor is organized to allow for the production of different transcripts via alternative splicing of D3 receptor heteronuclear-RNA (hn RNA or pre-mRNA) in the cell nucleus, as illustrated in Figure 1 (Griffon et al, 1996;Fu et al, 1995;Giros et al, 1991;Park et al, 1995). At least seven distinct alternatively spliced D3 receptor variants are produced, including the full-length D3 receptor (called 'D3'), and a shorter receptor isoform, D3S, lacking 21 amino acids within the third cytoplasmic loop (Fishburn et al, 1993).…”
Section: D3 Dopamine Receptor Alternative Splicingmentioning
confidence: 99%
“…[60][61][62][63] Primers and conditions used for amplification of the d4 receptor were as previously published. 32 In addition, primers were not designed within known polymorphic coding regions such as for the 5ht2a and 5ht6 receptors.…”
Section: Rna Extraction and First Strand Cdna Synthesismentioning
confidence: 99%